Color It Real: A Program to Increase Condom Use and Reduce Substance Abuse and Perceived Stress - Zellner, Tiffany (Int J Environ Res Public Health, 2015)
Few interventions have targeted perceived stress as a co-occurring construct central to substance use and subsequent HIV/AIDS risk reduction among African American urban young adults. The Color It Real Program was a seven session, weekly administered age-specific and culturally-tailored intervention designed to provide substance abuse and HIV education and reduce perceived stress among African Americans ages 18 to 24 in Atlanta, GA. Effectiveness was assessed through a quasi-experimental study design that consisted of intervention (n = 122) and comparison (n = 70) groups completing a pre- and post-intervention survey. A series of Analysis of Variance (ANOVA) tests were used to assess pre- to post-intervention changes between study groups. For intervention participants, perceived stress levels were significantly reduced by the end of the intervention (t(70) = 2.38, p = 0.020), condom use at last sexual encounter significantly increased (F = 4.43, p = 0.0360), intervention participants were significantly less likely to drink five or more alcoholic drinks in one sitting (F = 5.10, p = 0.0245), and to use clean needles when injecting the drug (F = 36.99, p = 0.0001). This study is among the first of its kind to incorporate stress management as an integral approach to HIV/SA prevention. The program has implications for the design of other community-based, holistic approaches to addressing substance use and risky behaviors for young adults.